Co-adsorption performance and mechanism of nitrogen and phosphorus onto eupatorium adenophorum biochar in water. (November 2021) - Cheng, Ning; Wang, Bing; Feng, Qianwei; Zhang, Xueyang; Chen, Miao
Graphical abstract: Highlights: EBC can co-adsorb ammonium and phosphate in water. Low pyrolysis temperature and alkaline condition are beneficial for the adsorption. Sorption mechanisms are electrostatic attraction, precipitation, ligand exchange. Site energy analysis indicates that electrostatic attraction is the main mechanism. Abstract: To reduce the eutrophication caused by nitrogen and phosphorus in water, invasive plant Eupatorium adenophorum was used to prepare biochar under different pyrolysis temperatures for the co-adsorption of nitrogen and phosphorus. The influencing factors of the co-adsorption of ammonium and phosphate onto EBC and its adsorption mechanism were systematically studied. The results show that Eupatorium adenophorum biochar (EBC) has rich functional groups and high specific surface area. Low pyrolysis temperature (300 °C) and alkaline conditions are beneficial for the co-adsorption. The adsorption of ammonium and phosphate by EBC is more in line with the pseudo-second-order kinetics and Langmuir-Freundlich model (Qmax is 2.32 mg P/g and 1.909 mg N/g). Site energy analysis further confirms that electrostatic attraction is the main mechanism. This study shows that EBC could be used as a low-cost and effective adsorbent to simultaneously remove ammonium and phosphate from water, providing a method for resource utilization of invasive plants.